Study of the Efficacy of Malathion Impregnated Cotton Cords in Housefly Control - Kochhar, R. K.; Dixit, R. S.; Somaya, C. I. (Defence Science Journal, 2014)
A comparative study on the efficacy of malathion impregnated cords on 13 mm and 22 mm circumference in housefly control has been carried. The results have shown that 13 mm cord is more economical weight for weight, but both afford protection from four to five months. Other factors like temperature and humidity which influence the efficacy of cords are discussed.